2003
DOI: 10.1124/dmd.31.10.1199
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolism of the Tobacco-Specific Nitrosamines 4-(Methylnitrosamino)-1-(3-Pyridyl)-1-Butanone and 4-(Methylnitrosamino)-1-(3-Pyridyl)-1-Butanol by Rat Cytochrome P450 2a3 and Human Cytochrome P450 2a13

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and its carbonyl-reduction product, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), are potent lung carcinogens in rats and are presumed human lung carcinogens. NNK and NNAL are bioactivated to DNA-binding intermediates via hydroxylation of the carbon atoms adjacent to the nitroso moiety (i.e., ␣-hydroxylation) by cytochrome P450s (P450s). Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 10 publications
5
54
0
Order By: Relevance
“…Urinary NNAL levels from exposure to secondhand smoke is about 30 times lower than from exposure to active smoking (24), and there is little information that suggests that TTFC might be related to exposure to secondhand smoke in active smokers. The major metabolic activation pathways of NNK and its proximate metabolite NNAL occur by a-hydroxylation, whereas the detoxification of NNAL to NNAL-Gluc occurs by glucuronidation (25). While there may be interindividual differences in the metabolism of NNK and NNAL, NNAL is an excellent indicator of tobacco carcinogen exposure and particularly useful in epidemiologic studies because unlike many other known tobacco carcinogens, it is not found in other environmental sources.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary NNAL levels from exposure to secondhand smoke is about 30 times lower than from exposure to active smoking (24), and there is little information that suggests that TTFC might be related to exposure to secondhand smoke in active smokers. The major metabolic activation pathways of NNK and its proximate metabolite NNAL occur by a-hydroxylation, whereas the detoxification of NNAL to NNAL-Gluc occurs by glucuronidation (25). While there may be interindividual differences in the metabolism of NNK and NNAL, NNAL is an excellent indicator of tobacco carcinogen exposure and particularly useful in epidemiologic studies because unlike many other known tobacco carcinogens, it is not found in other environmental sources.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in NNK and NNAL metabolism may be due to differences in the affinity of different P450 isoforms for NNK versus NNAL as a result of differences in polarity between the keto group of NNK and the hydroxyl group of NNAL. In fact, Jalas et al (2003) found that CYP2A enzymes are more efficient catalysts of NNK metabolism than of NNAL metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Although a solution initially containing a 1:1 ratio of CYP2A13 to cytochrome b 5 was used to grow the crystals, and density weakly suggestive of cytochrome b 5 was present in the channels of the P450 crystalline lattice, it was not strong enough to model cytochrome b 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Structures of CYP2A13 with NNK Bound-NNK can be oxidized by CYP2A13 at either carbon ␣ to the nitrosamine. The dominant metabolite (5, 7, 9) results from hydroxylation of the ␣-methylene, but the ␣-methyl can also be hydroxylated with about a 3-fold lower K cat /K m (5,7,9). NNK bound to CYP2A13 in two different orientations in different molecules of the CYP2A13/NNK P1 structure and in yet another orientation in the CYP2A13/NNK I422 structure.…”
Section: Dissociation Constants For Nicotine and Nnk-nicotinementioning
confidence: 99%